Alexithymia and Sensory Processing Sensitivity: Areas of Overlap and Links to Sensory Processing Styles - Jakobson, Lorna S.; Rigby, Sarah N. (Frontiers in Psychology, 2021)
Alexithymia is a dimensional trait characterized by difficulties identifying and describing feelings (DIF, DDF) and an externally-oriented thinking (EOT) style. Here, we explored interrelationships between alexithymia and measures assessing how individuals process and regulate their responses to environmental and body-based cues. Young adults (N = 201) completed self-report questionnaires assessing alexithymia, sensory processing sensitivity (SPS), interoceptive accuracy (IA), sensory processing styles, and current levels of depression, anxiety, and stress. Whereas EOT was related to low orienting sensitivity, problems with emotional appraisal (DIF/DDF) were related to heightened sensory sensitivity. In addition, features of SPS improved prediction of alexithymia above and beyond that accounted for by IA. We suggest that EOT is linked to problems maintaining a representation of one’s emotions in working memory, and that low IA and problems with emotional appraisal are linked to atypicalities in sensory processing that may impact embodiment. A latent profile analysis revealed five classes of individuals distinguished by the relative strength of different alexithymic traits, and by differences in IA and sensory processing styles. The classes identified included two lexithymic, one modal, and two alexithymic groups, showing different susceptibilities to SPS. Overall, our findings lend support to the view that alexithymia is associated with atypicalities in both bottom-up and top-down problems that impact emotion processing and regulation. They also raise the possibility that individuals with different alexithymia subtypes may differ with regard to a range of factors including not only SPS but also early life experiences, mental health outcomes, and susceptibility to various personality disorders.